Walt Disney's Lady and the Tramp - Slater, Teddy; Dias, Ron; Langley, Bill (Great Britian Cemtum books ltd, 2018)
When mean Aunt Sarah takes over a cocker spaniel's once-happy home, the dog flees and experiences some dangerous moments before her hero, Tramp, arrives on the scene
English stories
1 2
Keywords: Dogs -- Fiction